Comparison of adsorptive with extractive stripping voltammetry in electrochemical determination of retinol - Sýs, Milan; Žabčíková, Simona; Červenka, Libor; Vytřas, Karel (My University, 2017)
Adsorptive stripping voltammetry (AdSV) of retinol at solid glassy carbon electrode (GCE), carbon paste electrode (CPE) covered by thin layer of multi-wall carbon nanotubes (CPE/MWCNTs) and carbon paste electrode covered by thin layer of single layer graphene (CPE/Graphene) was compared with an extractive stripping voltammetry (ExSV) into silicone oil (SO) as lipophilic binder of glassy carbon paste electrode (GCPE). All types of selected working electrodes were characterized by a scanning electron microscopy to determine overall morphology of electrode surfaces together with spatial arrangement of used carbon particles. The retinol, also known as vitamin A1, was chosen as a model analyte because it is the most biologically active representative of retinoids which are classified as a significant group of lipophilic vitamins. Based on this comparison, it was observed that electrochemical method with high sensitivity (ExSV at GPCE) is generally characterized by shorter linear range of the calibration curve than in case of AdSV at CPE/MWCNTs or CPE/Graphene. Unlike AdSV at solid GCE, all other tested electrochemical methods could represent suitable analytical tools for monitoring of retinoids in different types of foodstuffs. Especially, content of retinol up to tenths milligrams can be easily determined using ExSV. Additionally, negative interference of chemical species present in real samples is minimal in comparison with direct voltammetric methods performed in supporting electrolytes based on organic solvents due to application of accumulation step in „ex-situ“ mode.
Srovnání adsorptivní s extraktivní voltametrií při elektrochemickém stanovení retinolu
Keywords: Adsorptive voltammetry; carbon nanotubes; extractive voltammetry; glassy carbon; graphene; retinol; Adsorptivní voltametrie; uhlíkové nanotrubice; extraktivní voltametrie; skelný uhlík; grafen; retinol